Versifying adversity: Using dramaturgically framed poetic inquiry to explore complexity in the second language learning experience. (November 2022) - Gillies, Hamish; Roger, Peter
Abstract: Over the past 15 years, research in the field of second language learning motivation has been dominated by the second language (L2) motivational self system, conceptualizing motivation as a combination of the ideal L2 self, ought-to L2 self, and L2 learning experience . Despite the analytical strength demonstrated by the self components of the L2 motivational self system, the influential role of the L2 learning experience component is still in need of greater elucidation. Using a hybridized research approach combining a complex dynamic systems (CDS) perspective with dramaturgical coding and poetic inquiry, we unpack a Japanese undergraduate student's L2 learning experience. Taking the learner as both a complex system and a situated actor, key themes are identified and explored as attractor states. Humanizing what can often be an impersonal perspective, dramaturgically framed poetic inquiry is seen to add analytical power to the CDS perspective and afford its artistic and evocative representation.